2013
DOI: 10.1371/journal.pone.0073621
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion to Carbon Nanotube Conductive Scaffolds Forces Action-Potential Appearance in Immature Rat Spinal Neurons

Abstract: In the last decade, carbon nanotube growth substrates have been used to investigate neurons and neuronal networks formation in vitro when guided by artificial nano-scaled cues. Besides, nanotube-based interfaces are being developed, such as prosthesis for monitoring brain activity. We recently described how carbon nanotube substrates alter the electrophysiological and synaptic responses of hippocampal neurons in culture. This observation highlighted the exceptional ability of this material in interfering with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 83 publications
1
40
0
Order By: Relevance
“…In addition, cells were plated on graphene composites, graphene oxides, or on reduced graphene oxides with different surface charges and degree of electrical, photo, and laser stimulation (Akhavan and Ghaderi, 2013a,b, 2014; Tu et al, 2013a, 2014; Akhavan et al, 2014, 2015; Guo et al, 2016a). Similarly, both uncoated and coated functionalized single-walled CNTs (SWCNTs) and multi-walled CNTs (MWCNTs) as well as aligned CNTs and nanofibers have been reported to permit and stimulate neuronal growth and the formation of active synaptic contacts (Jan and Kotov, 2007; Malarkey et al, 2009; Cellot et al, 2011; Jin et al, 2011; Fabbro et al, 2013; Gupta et al, 2015; Vicentini et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, cells were plated on graphene composites, graphene oxides, or on reduced graphene oxides with different surface charges and degree of electrical, photo, and laser stimulation (Akhavan and Ghaderi, 2013a,b, 2014; Tu et al, 2013a, 2014; Akhavan et al, 2014, 2015; Guo et al, 2016a). Similarly, both uncoated and coated functionalized single-walled CNTs (SWCNTs) and multi-walled CNTs (MWCNTs) as well as aligned CNTs and nanofibers have been reported to permit and stimulate neuronal growth and the formation of active synaptic contacts (Jan and Kotov, 2007; Malarkey et al, 2009; Cellot et al, 2011; Jin et al, 2011; Fabbro et al, 2013; Gupta et al, 2015; Vicentini et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Further, the microarray studies suggested the presence of the active repair process involving microglia in the absence of reactive gliosis. 65 Nanotechnology approaches can also be used to regenerate chronically injured nerve cells. An interesting study has shown that the incorporation of electrospun nanofibers, self-assembling peptides, and proregenerative cytokines into guidance channels of the chronic spinal cord injured rat model resulted in a well-developed vascular network, basal lamina, and myelin, which eventually leads to enhanced electrophysiological recovery.…”
mentioning
confidence: 99%
“…155 In another study, immature spinal cord neurons isolated from neonatal rat spinal cords showed rapid growth on pyrolidine-functionalized MWCNT coated surfaces. 156 In an in vivo study, electrospun collagen-PCL-MWCNT fibrous scaffolds were shown to assist in the recovery of rat sciatic nerve defect models and prevented muscle atrophy. In the same study, the scaffold also supported Schwann cell adhesion and elongation.…”
Section: Neural Regenerationmentioning
confidence: 99%